2014
DOI: 10.1098/rsif.2014.0520
|View full text |Cite
|
Sign up to set email alerts
|

Design and control of compliant tensegrity robots through simulation and hardware validation

Abstract: , has developed and validated two software environments for the analysis, simulation and design of tensegrity robots. These tools, along with new control methodologies and the modular hardware components developed to validate them, are presented as a system for the design of actuated tensegrity structures. As evidenced from their appearance in many biological systems, tensegrity ('tensile-integrity') structures have unique physical properties that make them ideal for interaction with uncertain environments. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
143
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(152 citation statements)
references
References 43 publications
0
143
0
1
Order By: Relevance
“…Further deformations move the CoM to the next position, allowing the robot to move in different directions. To explore the interaction between tensegrity robots and the environment, software design platforms were presented in [134] with the aim of exploiting these robots' abilities. Similarly, the jamming behaviour of a skin stuffed with granular material has been exploited to deform a soft ball-like robot and achieve omnidirectional locomotion [135].…”
Section: Alternative Modes Of Locomotionmentioning
confidence: 99%
“…Further deformations move the CoM to the next position, allowing the robot to move in different directions. To explore the interaction between tensegrity robots and the environment, software design platforms were presented in [134] with the aim of exploiting these robots' abilities. Similarly, the jamming behaviour of a skin stuffed with granular material has been exploited to deform a soft ball-like robot and achieve omnidirectional locomotion [135].…”
Section: Alternative Modes Of Locomotionmentioning
confidence: 99%
“…In earlier work [9], [17], it was shown that for a tensegrity robot, a linear transformation from the sensor signals to the motor signals was enough to generate stable locomotion. The idea behind this is that the body of the robot itself has computing power, and that this power is being harvested by using it as a reservoir.…”
Section: A Embodied Computationmentioning
confidence: 99%
“…While physical implementations exist ranging from a water bucket [15] to integrated photonics devices [16], robotic implementations are rare. Nevertheless, recent work [9], [17] illustrated that locomotion control can be outsourced to the body of a tensegrity robot: a structure composed of compression elements held together by a compliant tensile network. Stable gait generation was achieved by using only optimized linear feedback from the robot's stretch sensors to its actuator control signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final design was inspired by the tensegrity robotics work at the Intelligent Robotics group at nAsA's Ames Research Center, in collaboration with a number of international universities [CDI+14]. The term tensegrity refers to tensional integrity, where the components, such as trusses, are isolated and under constant compression, provided by continuous tension from connecting cables.…”
Section: Fig 8: Chair Concept From the First Iteration Cycle (A) To mentioning
confidence: 99%